2012
DOI: 10.1080/02786826.2012.704098
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Spray Atomization for a Nasal Spray Device

Abstract: The purpose of this work is to evaluate numerical modeling techniques for simulation of spray atomization from a nasal spray device to complement experimental measurements previously. In the past, spray breakup models have not been applied to nasal spray applications, but rather for high-pressure applications such as combustion, and industry and agricultural spraying. The parameters in breakup model were not optimized for this kind of low-pressure injection with small-scale atomizer. Thus, there is a need to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…According to Fung et al, (26) fine droplets are transported and dispersed throughout the spray from the presence of turbulent eddies in the flow. These droplets quickly lose their momentum and become entrained in the flow field.…”
Section: Droplet Size Analysismentioning
confidence: 99%
“…According to Fung et al, (26) fine droplets are transported and dispersed throughout the spray from the presence of turbulent eddies in the flow. These droplets quickly lose their momentum and become entrained in the flow field.…”
Section: Droplet Size Analysismentioning
confidence: 99%
“…Since then computational studies have investigated its anatomical form, airflow patterns, and fluid-particle interactions to gain a better understanding of: respiration function [7][8][9][10]; airconditioning [11,12]; and surgical implications [13][14][15][16][17]. When a secondary particle phase is introduced, inhaled particles coupled to the airflow field, allow studies of nasal drug delivery [18][19][20][21][22]; and inhalation toxicology [23][24][25] or general particle deposition studies [26,27]. The work by Wang et al [28] indicated deposition efficiency for 22 lm particles in the nasal cavity reached 100% for light breathing and revealed deposition hot spots for micron-particles.…”
Section: Introductionmentioning
confidence: 99%
“…Other computational studies include: Keeler et al [17] who investigated the influence of nasal airway geometry from different ethnic groups on spray particle deposition and found that white and Latin Americans had the least patent nasal cavity, although this was based on four models per ethnic group; Kiaee et al [18] that found particle diameter and particle injection speed, were the dominant parameters (other parameters were spray cone angle, spray release direction, and particle injection location) that influenced deposition in seven adult nasal airways; and Fung et al [19] performed CFD modelling to characterise the nasal spray atomization stage. Djupesland et al [20] showed a bi-directional nasal delivery concept reduced lung deposition by taking advantage of the posterior connection between the nasal passages persisting when the soft palate automatically closes during oral exhalation.…”
Section: Introductionmentioning
confidence: 99%